The mundanity of translanguaging and Aboriginal identity in Australia - Tankosić, Ana; Dovchin, Sender; Oliver, Rhonda; Exell, Mike (2022)
Drawing on ethnographic interview analysis of Aboriginal participants in Australia, this study seeks to expand the critical discussions in Applied Linguistics by understanding the concept of translanguaging in relation to its “mundanity” (or ordinariness). Our data shows that rather than perceiving translanguaging as extraordinary, for Aboriginal speakers it is more likely to be considered normal, unremarkable, mundane, and as a long-existing phenomenon. The concept of the mundanity of translanguaging is thereby expanded through three main discussions in this article: 1) negotiating identity and resisting racism, where the Aboriginal speakers choose to translanguage using their full linguistic repertoires, but with appropriate communicative adjustments made for their interlocutor; 2) a display of respect towards their land, heritage and language; and 3) as an inherent and mundane everyday practice where they constantly negotiate between heritage languages, English, Kriol, and Aboriginal English varieties. The significance of this study lies in the normalisation of translanguaging as a mundane disinvention strategy, as this urges us to perceive linguistic separateness as a colonial ideological construct that is used to exhibit control over diverse peoples and to maintain uniformity and stability of nation-states.